Factors influencing the rate of formation of tree‐related microhabitats and implications for biodiversity conservation and forest management. Issue 2 (7th November 2021) - Courbaud, Benoit; Larrieu, Laurent; Kozak, Daniel; Kraus, Daniel; Lachat, Thibault; Ladet, Sylvie; Müller, Jörg; Paillet, Yoan; Sagheb‐Talebi, Khosro; Schuck, Andreas; Stillhard, Jonas; Svoboda, Miroslav; et al.
Abstract: The retention of trees bearing tree‐related microhabitats (TreMs) has become an important means of conserving biodiversity in production forests. However, we lack estimates of TreM formation rates and evidence on factors driving TreM formation. Based on the observation of 80, 099 living trees from 19 species groups in Europe and Iran, we estimated the probability of TreM occurrence on trees and the associated rate of first TreM formation as a function of tree DBH, management, tree species group and random site effects. We built a separate model for each of 11 TreM groups. The hazard rate of first TreM formation (defined as the probability of formation of a first TreM forming on a tree that is known to have none, during an infinitesimal DBH increment) increased with DBH for some TreM groups like breeding‐woodpecker‐hole, rot‐hole or root‐concavity, indicating an acceleration in TreM formation during tree growth. However, it decreased with DBH for TreM groups like bark‐loss or dendrotelm, indicating slower formation on very large trees. Most TreM groups had reduced formation rates in managed forests (last logging less than 100 years ago) compared to unmanaged forests (no logging for at least 100 years), with the exception of dendrotelms . No general difference appeared between broadleaves and conifers, but early‐successional species tended to have different TreMs than mid‐ and late‐successional species. Abies, Alnus, Betula, Fagus, Prunus, Quercus, Sorbus, Tilia and Ulmus displayed high formation rates for six TreM groups or more. Variability among sites was considerable. Synthesis and applications . The rate of formation of tree‐related microhabitats (TreMs) varies greatly among TreM groups, tree species, locations, tree diameters at breast height and forest management. The high rate of formation of some TeM groups on small trees implies that tree retention for biodiversity should concern trees of all sizes and start as soon as thinning operations have occurred. Biodiversity conservation should value not only forest stands and trees that already have many TreMs but also those where the likelihood of future TreM formation is high due to species, maturity or local environmental conditions. The addition of quantitative models of TreM formation to forest stand dynamics simulators is necessary to better take into account biodiversity conservation in forest management. Abstract : The rate of formation of tree‐related microhabitats (TreMs) varies greatly among TreM groups, tree species, locations, tree diameters at breast height and forest management. The high rate of formation of some TeM groups on small trees implies that tree retention for biodiversity should concern trees of all sizes and start as soon as thinning operations have occurred. Biodiversity conservation should value not only forest stands and trees that already have many TreMs but also those where the likelihood of future TreM formation is high due to species, maturity or local environmental conditions. The addition of quantitative models of TreM formation to forest stand dynamics simulators is necessary to better take into account biodiversity conservation in forest management. Résumé: La rétention d'arbres portant des dendromicrohabitats est devenue un moyen important de conserver la biodiversité dans les forêts de production. Cependant, nous manquons d'estimations des taux de formation des dendromicrohabitats et de connaissance sur les facteurs de variations de ces taux de formation. Sur la base de l'observation de 80 099 arbres vivants appartenant à 19 groupes d'espèces en Europe et en Iran, nous avons estimé la probabilité d'apparition de dendromicrohabitats sur les arbres et le taux de formation d'un premier dendromicrohabitat en fonction du diamètre de l'arbre, du groupe d'espèces d'arbres, de la gestion, et d'effets aléatoires correspondants aux sites. Nous avons construit des modèles distincts pour 11 groupes de dendromicrohabitats. Le taux de hasard de formation du premier dendromicrohabitat (défini comme la probabilité de formation d'un premier dendromicrohabitat sur un arbre, dont on sait qu'il n'en porte pas, pendant un accroissement en diamètre infinitésimal) augmente avec le diamètre pour certains groupes de dendromicrohabitats comme les loges de reproduction de pic, les cavités à terreau ou les concavités racinaires, indiquant une accélération de la formation de ces dendromicrohabitats pendant la croissance de l'arbre. En revanche, il diminue avec le diamètre pour les groupes de dendromicrohabitats tels que les zones sans écorce ou les dendrotelmes, indiquant une formation plus lente sur les très grands arbres. La plupart des groupes de dendromicrohabitats présentent des taux de formation réduits dans les forêts gérées (dernière exploitation forestière depuis moins de 100 ans) par rapport aux forêts non gérées (aucune exploitation forestière depuis au moins 100 ans), à l'exception des dendrotelmes. Aucune différence générale n'est apparue entre les feuillus et les conifères, mais les espèces en début de succession ont tendance à avoir des dendromicrohabitats différents des espèces en milieu et fin de succession. Abies, Alnus, Betula, Fagus, Prunus, Quercus, Sorbus, Tilia et Ulmus présentent des taux de formation élevés pour six groupes de dendromicrohabitats ou plus. La variabilité entre les sites est considérable. Synthèse et applications : Le taux de formation des dendromicrohabitats varie considérablement selon les groupes de dendromicrohabitats, les espèces d'arbres, les sites, le diamètre des arbres et la gestion forestière. Le taux élevé de formation de certains groupes de dendromicrohabitats sur de petits arbres implique que la conservation de certains arbres pour la biodiversité devrait concerner des arbres de toutes tailles et commencer dès que les premières opérations d'éclaircie. La conservation de la biodiversité devrait valoriser non seulement les peuplements forestiers et les arbres qui présentent déjà de nombreux dendromicrohabitats, mais également ceux où la probabilité de formation future de dendromicrohabitats est élevée en raison de l'espèce, de la maturité ou des conditions environnementales locales. L'ajout de modèles quantitatifs de formation de dendromicrohabitats aux simulateurs de dynamique de peuplements forestiers est nécessaire pour mieux prendre en compte la conservation de la biodiversité dans la gestion forestière.